The role of visual and direct force feedback in robotics‐assisted mitral valve annuloplasty. Issue 3 (16th November 2016) - Currie, Maria E.; Talasaz, Ali; Rayman, Reiza; Chu, Michael W.A.; Kiaii, Bob; Peters, Terry; Trejos, Ana Luisa; Patel, Rajni
Abstract: Background: The objective of this work was to determine the effect of both direct force feedback and visual force feedback on the amount of force applied to mitral valve tissue during ex vivo robotics‐assisted mitral valve annuloplasty. Methods: A force feedback‐enabled master–slave surgical system was developed to provide both visual and direct force feedback during robotics‐assisted cardiac surgery. This system measured the amount of force applied by novice and expert surgeons to cardiac tissue during ex vivo mitral valve annuloplasty repair. Results: The addition of visual (2.16 ± 1.67), direct (1.62 ± 0.86), or both visual and direct force feedback (2.15 ± 1.08) resulted in lower mean maximum force applied to mitral valve tissue while suturing compared with no force feedback (3.34 ± 1.93 N; P < 0.05). Conclusions: To achieve better control of interaction forces on cardiac tissue during robotics‐assisted mitral valve annuloplasty suturing, force feedback may be required.